Peripherality in the global container shipping network : The case of the Southern African container port system - (:unkn) unknown (My University, 2016)
Regional trade co-operation, economic growth and greater political stability have enabled increased container throughput and container port capacity development. Earlier academic work has indicated that the functional position of this port region in the global maritime network might be shifting from a remote region in the periphery of the network to a more intermediate position. This paper aims to analyze the changing level of peripherality and remoteness of the Southern African container port system as part of the global container shipping network. The central hypothesis is that Southern Africa has moved from a remote shipping region to a more central shipping region in the global network. The methodology consists of the calculation of network measures for Southern African ports. The changing geographical distribution of flows among the main container ports in South Africa, Namibia, Mozambique, Mauritius and Madagascar will also be explored in terms of their respective shipping services, port calling patterns, market structure (in terms of the number of active carriers) and the up-scaling of vessel and port capacity. The overall result is a mapped port hierarchical structure with a clear indication of the shifted maritime centrality of Southern African ports from 1996 to the present decade.
Keywords: African Research